P-Y Curve Correction of Shallow Seabed Formation Containing Hydrate - Haoyu Diao; Honghai Fan; Rongyi Ji; Bangchen Wu; Yuguang Ye; Yuhan Liu; Fei Zhou; Yixiang Yang; Zhi Yan (Energies, 2023)
With the continuous growth in global energy demand, the exploration and development of hydrates has been the focus of increasing attention, and the accurate evaluation of the mechanical properties of hydrate layers has become particularly important. In this study, using a self-developed hydrate sample preparation device and hydrate triaxial seepage test platform, triaxial shear tests were carried out using the in situ synthesis method for hydrate sediment in the laboratory, and the stress–strain curves of hydrate sediment with different levels of saturation were obtained. By analyzing the stress–strain curve, the mechanical parameters of hydrate sediment were calculated and simulated using ABAQUS (2021, Dassault systemes, Vélizy Villacoublay France) finite element software. Several p-y curves were calculated and compared with the simulation results, and the p-y curve correction method of the hydrate layer in a shallow seabed was obtained. It was found that the strength of the hydrate sediment increased with an increase in saturation. At the same time, an increase in confining pressure and a decrease in temperature also increased the strength of hydrate deposits. Through comparison with the existing API (American Petroleum Institute) standard p-y curve, it was found that its strength is low because the existence of the hydrate improves the formation strength.